Influence of Age on Relationship with Websites - Santo, Pedro Espírito (2022)
E-commerce has grown quickly, and companies seek to attract their target audiences to their websites. The differences in behavior between young people, as users of websites and other older people is real. Thus, this investigation aimed to present an investigation model in order to analyze the determinants of loyalty to the sites and test the influence of age in this relationship. Through a sample of 250 website users, we tested an investigation model, tested through PLS-SEM, which supports the hypothesis that age produces effects in the relationship with the websites. This study is relevant for website managers, since it identifies the need for differentiated users. As impediment and limitations of the study discussed throughout this work.